Covid-19 in the African continent : sustainable development and socioeconomic shocks - Osabuohien, Evans, 1979-; Odularu, Gbadebo; Ufua, Daniel E.; Osabohien, Romanus (Emerald Publishing Limited, 2022)
COVID-19 in the African Continent examines the development, achievements, and challenges that have resulted owing to COVID-19 pandemic and how these precarious socioeconomic situations are being managed in African countries. This book explores the range of interventions aimed at mitigating the effects of COVID-19 by offering an in-depth understanding of the disruptive impacts of COVID-19 on the African continent. This edited collection underscores the nature and effects of non-health-related challenges such as environmental complexities and possible solutions to socioeconomic shocks caused by the COVID-19 pandemic along with other social, political, and economic distortions. Providing readers with a profound insight of the critical societal consequences of these challenges in African economies, this book covers the macroeconomic policy approaches adopted by government and non-governmental organisations to boost post-COVID-19 recovery and enhance a systemic process to facilitate the prospects for addressing socioeconomic shocks across the continent.